LA ANGUILA DE JARDÍN HETEROCONGER LONGISSIMUS GÜNTHER (PISCES: ANGUILLIFORMES, CONGRIDAE) EN LAS COSTAS DE VENEZUELA (Boletín de Investigaciones Marinas y Costeras, 2016)
The brown garden eel Heteroconger longissimus had been reported for Venezuela only by observations of sport divers. In this work we confirm the species for Venezuela based on the examination of four leptocephalous specimens deposited in the fish collection of the Academy of Natural Sciences of Philadelphia (ANSP) and five adult specimens collected recently by the authors and deposited in the Museo de Historia Natural La Salle (MHNLS), Caracas. In addition, we comment on the taxonomic status, distinctive characters, and habitat of the species.